PTH-221 Malnutrition in patients undergoing colorectal surgery as part of the enhanced recovery programme. (22nd June 2015) - Rye, B; Jenkins, JT; Culkin, A
Abstract : Introduction: Colorectal cancer (CRC) is the 4 th most common cancer in the UK. 1 The prevalence of malnutrition in CRC ranges from 2–48% depending on the definition used and stage of cancer. 2 Surgery is the primary treatment for CRC but may increase the risk of malnutrition by altering the metabolism of the patient. 3 Malnutriton before gastrointestinal surgery is associated with worse outcome. 4 Enhanced Recovery After Surgery (ERAS) aims to reduce the metabolic response to surgery promoting an earlier return to normal physiology. 5 The aim of this study was to examine the perioperative nutritional status of patients with CRC on an ERAS programme. Method: A prospective observational design was used. A nutritional assessment was completed in clinic before and after surgery. This included weight, height, BMI, percentage weight loss, tricep skinfold thickness, mid-arm muscle circumference, hand grip strength, five times sit to stand test and the malnutrition universal screening tool (MUST). A preoperative micronutrient blood test was taken. Descriptive statistics, paired sample t-test, multiple and linear regression were performed. Ethical approval was obtained. Results: Twenty-five patients were recruited. Table 1 shows the prevalence of malnutrition before and after surgery. Fifty-six percent of patients had vitamin D deficiency or insufficiency and 32% were anaemic preoperatively. Preoperative zinc and selenium levels were normal in all patients. Significant reductions in weight (-3.7 kg, p = 0.001) BMI (-1.3 kg/m², p = 0.001), mid-arm circumference (-1.5 cm, p = 0.001), tricep skinfold thickness (-1.2 mm, p = 0.004) and mid-arm muscle circumference (-1 cm, p-0.001) were found post-operatively. No significant changes in hand grip or sit to stand test were found. Preoperative BMI (p = 0.024), tricep skinfold thickness (p = 0.004) and hand grip strength (p = 0.028) may predict length of hospital stay but limited by sample size. Conclusion: Patients with CRC awaiting surgery are at risk of malnutrition, reduced functional capacity, vitamin D deficiency and anaemia. This study demonstrates patients on an ERAS programme experienced significant deteriorations in perioperative nutritional status. Preoperative nuritional assessment is able to identify patients at risk of malnutrition and may facilitate initiation of preoperative nutritional support. Disclosure of interest: None Declared. References: Cancer Research UK. Bowel Cancer 2014 [Online] Garth AK, et al. J Hum Nutr Diet 2010;23:393–401 Finnerty CC, et al. JPEN 2013;37:21–29 Jean-Claude M, et al. Clin Nutr 2012;31:896–902 Rao PKD, Haray PN. Surgery 2014;32 :185–189